The Clown of the Sciences: Theology at the Secular University - Abrahamse, Jan Martijn (Journal of European Baptist Studies, 2019)
Some ten years ago I was stopped by another student in the hallway of Amsterdam’s VU University and asked to complete a questionnaire, the exact nature of which I have completely forgotten. What I do remember is the look upon his face when I answered the question, “What are you studying at this university?” with “Theology”. His look was not just one of surprise, but wonder of a more desperate kind: he didn’t know what ‘theology’ was. Here was an intelligent student of about twenty years of age, at a university founded by Abraham Kuyper, of which theology was the founding faculty, who did not know what it was. Of course I explained it. Yet his bewilderment did not end there: “Is there an academic field that studies ‘God’?” he asked. Was I not joking? This article addresses the question of the role of theology and theologians in a secular environment, such as a university. Due to social changes theology is no longer the self-evident ‘Queen of the Sciences’, but is challenged to review its position among sciences, which often look with suspicion at its purposes. Instead of calling to reclaim the throne, and drawing on the historical figure of the Fool, it is argued that theology (or, rather theologians) should redress themselves as ‘Clowns of the Sciences’. By way of a conversation with the propositions of James McClendon and Stanley Hauerwas, a comic framework is set out that makes fun of the Queen, and thereby allows theology to participate by its oddity. Towards the end, and with the assistance of the prophet Jonah, a preliminary outline is made of the Clown’s Speech.